2020
DOI: 10.1016/j.neuroimage.2020.117192
|View full text |Cite
|
Sign up to set email alerts
|

Development and sex modulate visuospatial oscillatory dynamics in typically-developing children and adolescents

Abstract: Visuospatial processing is a cognitive function that is critical to navigating one’s surroundings and begins to develop during infancy. Extensive research has examined visuospatial processing in adults, but far less work has investigated how visuospatial processing and the underlying neurophysiology changes from childhood to early adolescence, which is a critical period of human development that is marked by the onset of puberty. In the current study, we examined behavioral performance and the oscillatory dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…The orchestrating function of pubertal hormones behind overall adolescent progress seems clear and assumes an explanatory role. Pubertal hormone levels are correlated with bone age [26][27][28] , time bodily growth 97 , cortical pruning 98,99 , and emotional 1,4 and cognitive 100,101 development in adolescence. The cascade of events during the pubertal transformation of a child into an adult is coordinated on individual timescales, and any attempt to assess adolescent brain and cognitive function requires the determination of the individual timescales.…”
Section: Discussionmentioning
confidence: 99%
“…The orchestrating function of pubertal hormones behind overall adolescent progress seems clear and assumes an explanatory role. Pubertal hormone levels are correlated with bone age [26][27][28] , time bodily growth 97 , cortical pruning 98,99 , and emotional 1,4 and cognitive 100,101 development in adolescence. The cascade of events during the pubertal transformation of a child into an adult is coordinated on individual timescales, and any attempt to assess adolescent brain and cognitive function requires the determination of the individual timescales.…”
Section: Discussionmentioning
confidence: 99%
“…The sexually dimorphic alpha responses identified in the present study again demonstrate female-specific recruitment of parietal association areas often involved in attention and higher-order processing, though unlike the gamma band results, these sex differences did not vary with age. Alpha activity has been documented to vary by age and sex during verbal working memory processing ( Embury et al, 2019 ); however, most MEG studies of cognitive development have observed these interactions in other frequency bands ( Fung et al, 2020 ; Killanin et al, 2020 ; Taylor et al, 2020 ). Future studies could utilize different visual stimuli or include further attentional manipulations to determine the extent to which alpha activity during basic visual perception exhibits developmental alterations, or whether such maturational effects are limited to more complex tasks and other oscillatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation of neural activity serving higher-order cognitive processing during adolescence has been extensively studied using fMRI (for review, see Casey et al, 2005 ; Rubia, 2013 ), and studies have identified sex-specific developmental patterns of cortical network activity during complex visuospatial processing tasks in youth, such as mental rotation and spatial working memory ( Hugdahl et al, 2006 ; Kucian et al, 2007 ; Schweinsburg et al, 2005 ). There is also a growing wealth of knowledge regarding changes in childhood neural oscillatory dynamics serving motor control ( Gaetz et al, 2010 ; Heinrichs-Graham et al, 2018 , 2020 ; Trevarrow et al, 2019 ; Wilson et al, 2010 ), higher-order cognition ( Embury et al, 2019 ; Taylor et al, 2020 ; 2021 ), and more complex visuospatial attention ( Fung et al, 2020 ; Killanin et al, 2020 ). Executing these tasks obviously requires input and integration of basic sensory information for successful performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found sex-specific lifetime maturation trajectories suggesting that biological maturation plays a major role in visual decision making. Neuroendocrine changes, especially the levels of sex steroid hormones are known to time bodily growth, emotional development and cortical pruning in adolescence [5, 56, 57], and seem to influence cognitive function during [58,59] and after the teenage years [60,61]. The fact that females peak earlier (around 19 years of age) than males (around 24 years of age) in maturation index in our study is in line with the known delay of puberty onset times in boys as compared to girls [62] and the relatively late peaks indicate a neotenous human-specific function, involving the latest maturing brain areas such as the prefrontal cortex and the precuneus [63, 64].…”
Section: Discussionmentioning
confidence: 99%